Ionophore-based potentiometric sensors for drug analysis - Khaled, Elmorsy; Abdel Ghahni, E.Y. (Univerzita Pardubice, 2012)
The construction, evaluation and analytical application of ionophore-based sensors for potentiometric determination of hexoprenaline sulphate (Hx) or biperiden hydrochloride (BP) are reported. Electrode matrices compositions are optimized on the basis of the nature and content of sensing ionophore, ionic sites and plasticizers. Sensors incroporated with β-cyclodextrins (β-CDs), sodium tetrakis (4-fluorophenyl) borate (NaTFPB) and 2-fluorophenyl 2-nitrophenyl ether (f-NPE), showed fast and stable potentiometric responses with mean Nernstian compliance of 59.0 ± 1.0 and 56.8 ± 1.4 mV·decade-1 for Hx and BP, respectively in the concentration ranges 1×10–5–1×10–2 mol·L–1 for Hx and 1×10–5–1×10–2 mol·L–1 for BP. Incorporation of β-CD as molecular recognition element improved the electrode sensitivity and¨selectivity due to encapsulation of the drug molecule into β-CD cavity (host-guest interaction). The electrodes were fully characterized in terms of composition, usable pH range, life span and response time. The developed electrodes have been successfully applied for the potentiometric determination of the cited drugs in pharmaceutical formulations. Comparison of the obtained results with those provided by reference methods revealed adequate accuracy for control assay.
Keywords: cyclodextrins; potentiometric sensors; hexoprenaline sulphate (Hx); biperiden hydrochloride (BP); pharmaceutical analysis